Improving the molecular diagnosis ofChlamydia psittaciandChlamydia abortusinfection with a species‐specific duplex real‐time PCR. Issue 10 (October 2015) - Opota, Onya; Jaton, Katia; Branley, James; Vanrompay, Daisy; Erard, Veronique; Borel, Nicole; Longbottom, David; Greub, Gilbert
Abstract : N/A: Chlamydia psittaci and Chlamydia abortus are closely related intracellular bacteria exhibiting different tissue tropism that may cause severe but distinct infection in humans. C. psittaci causes psittacosis, a respiratory zoonotic infection transmitted by birds. C. abortus is an abortigenic agent in small ruminants, which can also colonize the human placenta and lead to foetal death and miscarriage. Infections caused by C. psittaci and C. abortus are underestimated mainly due to diagnosis difficulties resulting from their strict intracellular growth. We developed a duplex real‐time PCR to detect and distinguish these two bacteria in clinical samples. The first PCR (PCR1) targeted a sequence of the 16S–23S rRNA operon allowing the detection of both C. psittaci and C. abortus . The second PCR (PCR2) targeted the coding DNA sequence CPSIT_0607 unique to C. psittaci . The two PCRs showed 100 % detection for ≥ 10 DNA copies per reaction (1000 copies ml − 1 ). Using a set of 120 samples, including bacterial reference strains, clinical specimens and infected cell culture material, we monitored 100 % sensitivity and 100 % specificity for the detection of C. psittaci and C. abortus for PCR1. When PCR1 was positive, PCR2 could discriminate C. psittaci from C. abortus with a positive predictive value of 100 % and a negative predictive value of 88 %. In conclusion, this new duplex PCR represents a low‐cost and time‐saving method with high‐throughput potential, expected to improve the routine diagnosis of psittacosis and pregnancy complication in large‐scale screening programs and also during outbreaks.